SHARIA-BASED ECONOMIC MANAGEMENT POLICIES IN POVERTY ALLEVIATION IN PIDIE DISTRICT, INDONESIA: Kebijakan Pemerintah Kabupaten Pidie Dalam Menurunkan Angka Kemiskinan - Dhaifanullah; Khairizzaman (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
Poverty is a multifaceted issue within a nation's existence. This situation also applies to District Pidie, an area in Aceh characterised by a significant poverty rate. This poverty issue is influenced by multiple indicators; therefore, a systematic and focused approach is required to address it effectively. This research aims to examine the policies of the Pidie Regency administration, the execution of these policies in addressing poverty, and the successful and effective measures implemented by the Pidie government to resolve poverty issues. This writing employs a qualitative descriptive research method. Data were acquired by observation, interviews, and documentation. The study findings revealed that the Pidie Government's poverty alleviation policy was organised around many strategies: right focus, right locus, right mode, right target, right amount, and right time. The adopted policies encompass elements seen as indices of poverty, specifically health, food, infrastructure, employment, and education. The execution of the Pidie Government's strategies to alleviate poverty is structured according to established indicators, including the allocation of individual land, acquisition of technological resources and infrastructure, scholarships for underprivileged children/groups, construction of educational facilities, provision of non-formal education resources, health insurance, support for individuals with disabilities, hospital referral services, regional development initiatives, autonomous village development, market operations, road construction, bridge construction, among others.